2014
DOI: 10.3233/jad-141371
|View full text |Cite
|
Sign up to set email alerts
|

General Public Perceptions and Attitudes toward Alzheimer's Disease from Five Cities in China

Abstract: Alzheimer's disease (AD) is the most common type of dementia affecting the aged population worldwide, yet its social perceptions have been less studied. To investigate the perceptions and attitudes toward AD in the Chinese population, a cross-sectional face-to-face survey of 2,000 randomly selected adults was conducted in five representative cities of China. This survey focused on the fear of AD, and the relationship between this variable and each studied factor was analyzed using univariate analysis and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
1
38
0
2
Order By: Relevance
“…This may partially be explained by the insidious presentations of dementia, since the gradual nature of the cognitive decline might be unrecognized by the family members living with them (Salloway and Correia, 2009;Dai et al, 2015). About 76.6% of Chinese had personal fear of AD (Zeng et al, 2015), but cognitive decline is commonly perceived as due to senility and normal aging (McCleary et al, 2013;Zeng et al, 2015). About 76.6% of Chinese had personal fear of AD (Zeng et al, 2015), but cognitive decline is commonly perceived as due to senility and normal aging (McCleary et al, 2013;Zeng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This may partially be explained by the insidious presentations of dementia, since the gradual nature of the cognitive decline might be unrecognized by the family members living with them (Salloway and Correia, 2009;Dai et al, 2015). About 76.6% of Chinese had personal fear of AD (Zeng et al, 2015), but cognitive decline is commonly perceived as due to senility and normal aging (McCleary et al, 2013;Zeng et al, 2015). About 76.6% of Chinese had personal fear of AD (Zeng et al, 2015), but cognitive decline is commonly perceived as due to senility and normal aging (McCleary et al, 2013;Zeng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived susceptibility and perceived severity about developing a disease are central components of health behavior research (Conner & Norman, 2005). Previous studies have explored people’s worry about developing AD and other dementias (Cutler, 2015; Cutler & Brăgaru, 2015; Kessler, Bowen, Baer, Froelich, & Wahl, 2012; Kinzer & Suhr, 2016; Roberts, McLaughlin, & Connell, 2014; Werner, 2002; Werner, Goldberg, Mandel, & Korczyn, 2013; Yeo, Horan, Jones, & Pendleton, 2007; Zeng et al, 2015). Some researchers found that participants’ worry changed with age (Cutler, 2015; Cutler & Brăgaru, 2015; Roberts et al, 2014), while others found no differences in worry across age groups (Yeo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There is suggestion that this may be beneficial to facilitate the early planning of care support and avoidance of 'crises' when the cognitive impairment starts to have a greater impact on inadequate family or carer support. Whilst in contrast the psychosocial implications, such as fear around loss of insurance, increased private health care premiums, loss of current employment and future employment opportunities, as well as relationship and family tensions which may culminate in social isolation and stigmatisation within wider society, have been widely reported within the literature [50,51,52]. Improved awareness of the consequence of mild cognitive impairment would appear an important precursor to prepare individuals before being screened with better information for family members, friends, employers and the government and public agencies is also required.…”
Section: Discussionmentioning
confidence: 99%